Biphasic Calcium Phosphate Bioceramics for Orthopaedic Reconstructions: Clinical Outcomes - Carlos A. Garrido; Sonja E. Lobo; Flávio M. Turíbio; Racquel Z. LeGeros (International Journal of Biomaterials)
BCP are considered the most promising biomaterials for bone reconstruction. This study aims at analyzing the outcomes of patients who received BCP as bone substitutes in orthopaedic surgeries. Sixty-six patients were categorized according to the etiology and morphology of the bone defects and received scores after clinical and radiographic evaluations. The final results corresponded to the combination of both parameters and varied from 5 (excellent result) to 2 or lower (poor result). Most of the patients who presented cavitary defects or bone losses due to prosthesis placement or revision, osteotomies, or arthrodesis showed good results, and some of them excellent results. However, patients with segmental defects equal or larger than 3 cm in length were classified as moderate results. This study established clinical parameters where the BCP alone can successfully support the osteogenic process and where the association with other tissue engineering strategies may be considered.